Hybridization of Indigenous Knowledge-Based Positivistic Governance - Yasin Limpo, Syahrul; Patittingi, Farida; Hasrul, Muh.; Yunus, Ahsan (International Journal of Psychosocial Rehabilitation, 2020)
The success or failure of democratic reform in Indonesia is a key question for Indonesia itself and for the surrounding region. Although Indonesia’s transition to democracy holds out the promise of good governance, this cannot be taken for granted as the recent practical governance is likely future challenges faced by Indonesia as it implements decentralization and provide some recommendations to improve the ongoing decentralization process. This article is a normative-legal research by using statute, case, and conceptual approaches. Meanwhile, data were analyzed descriptively, consisting of quotes. The results show that the practice of governance based on rather rigid State governance laws actually need to be hybridized with local wisdom (indigenous knowledge) in order to have a participatory spirit that can encourage active community participation in supporting government and development movements. This is a hybridization of Positivistic Constitutional Law with Indigenous Knowledge to formulate the complexity of the challenges faced by a government. Responsive governance supported by high community participation is the key to what we have achieved so far. This is possible as the hybridization of positivistic State administration law with indigenous knowledge in formulating policies as needed by the people.